Case reportSwimming pool granuloma – difficult diagnostic problem - Barańska-Rybak, Wioletta; Kozicka, Dorota; Lange, Magdalena; Sokołowska-Wojdyło, Małgorzata; Roszkiewicz, Jadwiga (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Swimming pool granuloma is a rare infection of the skin caused by Mycobacterium marinum. The primary skin lesion is defined as a blue/red papule or nodule with verrucous surface and secondary ulceration in some cases. The skin lesions are usually localized on upper limbs, especially fingers. Usually, at the very early beginning they are misdiagnosed as a deep mycotic infection, tuberculosis, skin abscess, leishmaniasis or warts. Here we analysed retrospectively 5 patients diagnosed and treated between June 2009 and September 2010 because of swimming pool granuloma in the Outpatient Ward of the Department of Dermatology, Medical University of Gdansk. We also followed the newest publications relating to this problem.